Factores de riesgo que influyen en la prevalencia de hipertensión arterial en adultos de la UMF 82 - Padilla Sandoval, Miriam Saraí (Universidad Michoacana de San Nicolas de Hidalgo, 2024)
Introduction. Arterial Hypertension (AHN) is a public health problem due to its high frequency and a risk factor for cardiovascular disease and other chronic diseases with high global morbidity and mortality. It is diagnosed with a persistent elevation of blood pressure greater than 140/90 mm/Hg. Objective. Identify the prevalence of AHN and related risk factors. Methods. Cross-sectional, prospective study, including subjects over 18 years of age, both genders, entitled to UMF No. 82, who attended as patients or companions of a relative. Their blood pressure was recorded and a questionnaire was required to identify risk factors that influence the development of AHN. Statistical analysis was performed using central tendency and dispersion tests. The association of risk factors was performed with logistic regression. A value of p<0.05 was considered statistically significant. Results. 357 subjects were studied. 189 women and 168 men. Average age 39.6 years. The prevalence of AHT was 32.2%. Age ? 40 years (OR= 2.441, IC95% 1.500-3.972, p<0.0001), smoking (OR= 1.779, IC95 1.136-2.786, p=0.012), overweight/obesity (OR=1.975, IC95% 1.121 -3.479, p= 0.019) and a history of macrosomia (OR= 2.446, 95% CI 1.164-5.141, p=0.018) were risk factors for AHT; It was also found that the patient with AHN had a higher frequency of SARS-CoV-2 infection (OR=2.404 adjusted for age, 95%CI 1.475-3.920, p<0.0001). Conclusion. The prevalence of AHN in the adult population assigned to the UMF No. 82 is high. Modifiable risk factors for AHN were found, which is why it is necessary to implement non-pharmacological and pharmacological strategies that have a beneficial impact and that are feasible to measure.

Introducción. La Hipertensión Arterial (HTA) es un problema de salud pública por su alta frecuencia y un factor de riesgo para enfermedad cardiovascular y otras enfermedades crónicas con alta morbimortalidad mundial. Se diagnostica con una elevación persistente de la presión arterial igual o mayor a 140/90 mm/Hg. Objetivo. Identificar los factores de riesgo que influyen la prevalencia de Hipertensión Arterial. Métodos. Estudio observacional, transversal, prospectivo, se incluyeron sujetos, mayores de 18 años, ambos géneros, derechohabientes a la UMF No. 82, que acudieron como pacientes o acompañantes de algún familiar. Se registró su presión arterial y se requisito un cuestionario para identificar factores de riesgo que influyen en el desarrollo de HTA. El análisis estadístico se realizó mediante pruebas de tendencia central y de dispersión. La asociación de los factores de riesgo se realizó con regresión logística. Se consideró de significancia estadística a un valor de p<0.05. Resultados. Se estudiaron 357 sujetos. 189 mujeres y 168 hombres. Edad promedio 39.6 años. La prevalencia de HTA fue del 32.2 %. La edad ? 40 años (OR= 2.441, IC95% 1.500-3.972, p<0.0001), el tabaquismo (OR= 1.779, IC95 1.136-2.786, p=0.012), el sobrepeso/obesidad (OR=1.975, IC95% 1.121-3.479, p= 0.019) y el antecedente de macrosomía (OR= 2.446, IC95% 1.164-5.141, p=0.018) fueron factores de riesgo para HTA; también se encontró que el antecedente de SARS-CoV-2 fue un factor de riesgo para desarrollar HTA (OR=2.404 ajustada por edad, IC95% 1.475-3.920, p<0.0001). Conclusión. La prevalencia de HTA en la población adulta adscrita a la UMF No. 82 es alta, Se encontraron factores de riesgo modificables para HTA por lo que son necesarias la implementación de estrategias no farmacológicas y farmacológicas que tengan un impacto benéfico para así prevenir la HTA.
Facultad de Ciencias Médicas y Biológicas. Especialidad en Medicina Familiar
Keywords: info:eu-repo/classification/cti/3; FCMB-E-2024-0085; Detección; Factores de riesgo; Hipertensión arterial; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/18724